Synthesis of silver nanoparticles using Solanum tuberosum peels’ extract and their activity against multi drug resistant bacteria - Kerai , Dhruti; Mbatia , Betty; Noah , Naumih (Algerian Journal of Biosciences, 2023)
Antimicrobial resistance is a global health concern. Nanoparticles are increasingly being used as an alternative to overcome microbial drug resistance. The synthesis of nanoparticles from crop residuals has the dual potential of combating antimicrobial resistance and addressing waste disposal challenges. In this study ethanolic extract from Solanum tuberosum peel varieties were investigated for the synthesis of silver nanoparticles (AgNPs) and their activity against methicillin-resistant Staphylococcus aureus and multidrug-resistant Escherichia coli evaluated. The formation of the AgNPs was confirmed using UV-Vis spectroscopy and Fourier Transform Infra-Red (FTIR) analysis, while size was confirmed using dynamic light scattering (DLS). Disc diffusion method was used to evaluate antimicrobial activity. Russet brown and red bliss potato peel varieties showed positive results for the presence of alkaloids, polyphenols, and flavonoids. UV-Vis spectroscopy of synthesized AgNPs showed prominent peaks at 435 and 430nm, while DLS showed a size of 391.5 and 203.00 nm for russet brown and red bliss, respectively. FTIR analysis for the crude extracts and nanoparticles showed a change in peaks, confirming that bio-reduction took place. Major peaks for brown russet nanoparticles were observed at 3337 cm-1, 1634 cm-1,1055 cm-1, while major peaks for red bliss nanoparticles were observed at 3330 cm-1, 1634 cm-1, and 1054 cm-1. Brown russet nanoparticles showed better activity against S. aureus, while red bliss nanoparticles had better activity against E. coli. Nanoparticles synthesized from both varieties showed antimicrobial activity against gram-positive and gram-negative bacteria